Estimation of the Degree of Entropy of Russia’s Foreign Economic Relations in the Choice of an International Industrial and Technological Partnership - Sopilko, Natalya; Bondarchuk, Nataliya; Margolina, Elena; Shcherbakova, Natalya; Stashevskayar, Nadegda (International Journal of Engineering and Technology, 2018)
The article studies the orderliness of Russia's foreign economic relations in the context of industrial and technological partnership with the other countries. The research is based on a combination of the logical-probabilistic approach of complex networks. It was noted that the issue of choosing the best ways for international production and technology cooperation should be resolved from the point of view of deliberate ordering in the most significant sectors for the planned outstripping development. The most significant industries for the Russian economy are identified: coal, oil and gas, machine building and high-tech sectors of the economy. The indicators of relatively low entropy (orderliness) of foreign economic relations in these significant areas are obtained. That means that there is a high potential for expanding the production and technology partnership. Although it was noted that Russia is not an active participant in industrial and technological integration with many countries in the world. The results of the study confirmed the possibility of using entropy indicators to assess the degree of development of foreign economic relations and determine the optimal directions of industrial and technological partnership.Â Â